Efecto de la sombra sobre el crecimiento y desarrollo del coquito (Cyperus rotundus L.) - Giraldo de Sendoya, Fabiola; Doll, Jerry D. (1976)
The effect of shade on the growth and development of purple nutsedge (Cyperus rotundus L.) was studied to determine the feasibility of integrating cultural control (shading) with other control methods. Pots with tubers from the Departments of Córdoba and Valle were placed under shades of 0, 44, 55, 62, 80, 87, 90 and 100 percent. The aerial portion was harvested 55 and 98 days after planting and the aerial and underground portions 139 days after planting. Shading had a negative effect on total dry matter production and plant number, especially with shades above 66 percent. Only with shades greater than 80 percent was tuber number greatly reduced. Plants under complete shade emerged but then died. No differences in growth were observed between tubers from the departments of Córdoba and Valle, (Colombia), indicating that ecotypes do not exist between these regions. Crops of maize, dry beans arid cassava gave 80 percent light interception at 35, 40 and 140 days after planting, respectively, in fields free of purple nutsedge. Therefore, the selection of the crop could greatly aid in the cultural control of this weed, such that maize and dry beans would compete much better with purple nutsedge than cassava.